A COMPARISON OF SECONDARY SCHOOL STUDENTS’ VALUE PERCEPTIONS IN TURKIYE AND THE UK - Çelebi, Celalettin; Yılmaz, Fatih; Izgar, Gökhan; Doğan, Mustafa (International Online Journal of Education and Teaching, 2022)
Values are concepts, related to personal or social preferences that are considered "good" such as beauty, honesty, love, honesty, loyalty and so on. The purpose of this research is to compare value perceptions of secondary school students studying in Türkiye and the UK. In this study, the cross-sectional method was adopted and 249 Turkish students studying in the UK, and 253 students studying in Türkiye participated. While the English form of The Positive Values Scale developed by Huang and Cornell (2016) was used as a data collection tool in the UK, the Turkish version of the same scale, adapted by Arslan (2018), was used in Türkiye. Since the data were not normally distributed, in the analysis, such techniques as arithmetic mean, standard deviation and Mann Whitney U tests have been used. According to the findings, a statistically significant difference was found in favor of the students in Türkiye. Additionally, a statistically significant difference was determined in favor of female students in the UK in the concern for others factor. However, there was no significant difference between the students in the UK and Türkiye in the overall scale and in its factors as far as gender was concerned.